The Role of the Cash Flow Statement in Enhancing the Quality of Financial Reporting in the General Tax Authority : An Applied Study - Hala Abdul Ameer Dhahir; Ahmed Rahi Abed; Nuha Aadi Abd Ali (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The percentage of Adequacy Flows Cash Operational and indicator Activity Operational and revenue on assets from the flow are two examples of cash flow events that help improve the quality of financial reporting. The research attempts to address the theoretical framework of the cash flow statement. According to the following premise, cash flow metrics have the potential to improve the quality of financial reporting. The Iraqi General Tax Authority for 2022 and 2023 serves as the study sample. The study came to several results, chief among them being that the cash flow list can offer Since these measures express the continuity of cash flows for the research sample, they would help improve the quality of financial reporting by measuring the quality of the sample's profits in a way that improves performance and is consistent with the variables supplementary the contemporary business environment for the research sample related to the Iraqi General Tax Authority.